Ecophysiology of sugarcane in the understory of Peltophorum dubium Spr. in agroforestry systems arrangements - Elli, Elvis Felipe; Caron, Braulio Otomar; de Paula, Gizelli Moiano; Eloy, Elder; Schwerz, Felipe; Schmidt, Denise (Comunicata Scientiae, 2017)
The objective of this study was to evaluate physiological and thermal aspects of sugarcane, in North and South oriented lines, in ‘canafístula’ understory under two plant arrangements in an agroforestry system. The experimental design was a completely randomized block in a 2x2x6 factorial, with two agroforestry systems (strip and line), two evaluation lines (North and South) and at six times a day (9am, 10am, 12pm, 2pm, 3pm and 4pm) with three repetitions. The evaluated characteristics were: incident photosynthetically active radiation (RFA), leaf temperature (TF), resistance to vapor diffusion (RS) and transpiration (E) using a digital porometer LI-1600 LI-COR. Analysis of variance revealed differences for the interaction of agroforestry system x evaluation line x time, for all variables. The physiological and thermal characteristics of sugarcane are influenced by plant arrangement, agroforestry system and the local evaluation within the system. The strip system lead to a higher available amount of RFA in its understory, which reflects in increased RS values and reduced E of sugarcane. The South line presented higher E for sugarcane in the morning period in strip system and lower during the afternoon for the line system, due to higher TF values.